2010
DOI: 10.1373/clinchem.2009.138164
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Increase of Cardiac Troponin I in Plasma without Evidence of Cardiac Injury

Abstract: CASEA 69-year-old man with diabetes mellitus type II, hypertension, dyslipidemia, and prior ischemic strokes presented to the emergency department with complaints of balance difficulties and inability to stand unassisted of 2 weeks' duration. The patient's home medication regimen included atenolol, lisinopril, amlodipine, metformin, and glipizide. He is a retired chef and a former smoker (20 pack-years). He has 2 brothers, both of whom had myocardial infarctions in their 50s. The patient's physical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…In addition, PEG precipitation does not identify the mechanism of the interaction between the monoclonal peak and cTnI. In addition, we did not demonstrate in the present case cTnI removal by protein A, protein G or antihuman immunoglobulin,3 as the clinical course of the patient including normal coronary angiography, did not motivate us to perform additional analyses. Nevertheless, PEG precipitation of IgG followed by other confirmatory techniques may help unveil the absence of ‘true’ increased serum cTnI concentration and avoid invasive procedures that may be harmful in these frail patients.…”
Section: Descriptioncontrasting
confidence: 66%
“…In addition, PEG precipitation does not identify the mechanism of the interaction between the monoclonal peak and cTnI. In addition, we did not demonstrate in the present case cTnI removal by protein A, protein G or antihuman immunoglobulin,3 as the clinical course of the patient including normal coronary angiography, did not motivate us to perform additional analyses. Nevertheless, PEG precipitation of IgG followed by other confirmatory techniques may help unveil the absence of ‘true’ increased serum cTnI concentration and avoid invasive procedures that may be harmful in these frail patients.…”
Section: Descriptioncontrasting
confidence: 66%
“…11 False-positive case reports have been widely reported in the recent literature though interestingly, the number of false-negative case reports is lower. 11,29 It is important also to re-emphasize that the effects of interference, either negative or positive, may persist for a long time depending on the underlying cause that triggered the production of interfering immunoglobulin antibodies. Protocols such as repeat analysis after 6 -12 h or 6 -18 h from onset may be unhelpful or even misleading if the initial reading is false.…”
Section: Or Simplymentioning
confidence: 99%
“…Domanski et al reported a case of a 62-year-old with persistently elevated troponin; he had extensive cardiac testing, including an angiogram, that was unrevealing, like our case [2]. Macrotroponin is a complex of immunoglobulin and cardiac troponin rarely reported in myeloma cases, COVID vaccination, and COVID infection and can falsely elevate troponin levels [2][3][4]. Adding polyethylene glycol to the patient's serum precipitates immunoglobulins, frees troponin molecules, and normalizes the troponin value [2][3][4].…”
Section: Discussionmentioning
confidence: 62%
“…It is also a red flag and a marker of increased mortality and morbidity in almost every condition associated with elevated troponin levels, such as sepsis, pulmonary embolism, tachycardia, anemia, stroke, and congestive heart failure [1]. Heterophil antibodies and autoantibodies can rarely interfere with high-sensitivity troponin assay causing falsely elevated troponin and myocardial infarction misdiagnosis [2][3][4].…”
Section: Introductionmentioning
confidence: 99%